2016
DOI: 10.3791/53926
|View full text |Cite
|
Sign up to set email alerts
|

Substantiating Appropriate Motion Capture Techniques for the Assessment of Nordic Walking Gait and Posture in Older Adults

Abstract: Nordic walking (NW) has become a safe and simple form of exercise in recent years, and in studying this gait pattern, various data collection techniques have been employed, each with positives and negatives. The aim was to determine the effect of NW on older adult gait and posture and to determine optimal use of different data collection systems in both short and long duration analysis. Gait and posture during NW and normal walking were assessed in 17 healthy older adults (age: 69 ± 7.3). Participants performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The observations of other authors, who showed an extension of double and single support during the NW gait of older adults compared to free walking (without poles), have also not been confirmed [13]. This may result from the study of people with various levels of physical fitness and the advancement of their NW technique, which significantly limits the possibility of a reliable comparison of the results obtained by different authors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The observations of other authors, who showed an extension of double and single support during the NW gait of older adults compared to free walking (without poles), have also not been confirmed [13]. This may result from the study of people with various levels of physical fitness and the advancement of their NW technique, which significantly limits the possibility of a reliable comparison of the results obtained by different authors.…”
Section: Discussionmentioning
confidence: 84%
“…In older individuals, NW resulted in longer strides and increased times of both double and single support compared to walking freely (without poles). During the NW gait, these people also had a lower walking speed and reduced step rate [13]. The literature demonstrates that NW reduces the load of the lumbar spine and lower limb joints and increases energy expenditure in comparison with recreational walking in older adults [14].…”
Section: Introductionmentioning
confidence: 94%
“…Firstly, the images were filtered and enhanced, and the image results were shown in Figure 7. 26,27 The accurate recognition rate and accurate positioning rate of the image can be obtained through the test. The results of five tests are counted and the results as shown in Table 3 28,29 are obtained.…”
Section: Experimental Design Of Robot Image Experimentsmentioning
confidence: 99%